DOOM'd to switch: superior cognitive flexibility in players of first person shooter games - Colzato, Lorenza S.; Van Leeuwen, Pieter J.; Van Den Wildenberg, Wery; Hommel, Bernhard (Frontiers in Psychology, 2010)
The interest in the influence of videogame experience on our daily life is constantly growing. “First Person Shooter” (FPS) games require players to develop a flexible mindset to rapidly react to fast moving visual and auditory stimuli, and to switch back and forth between different subtasks. This study investigated whether and to which degree experience with such videogames generalizes to other cognitive control tasks. Video game players (VGPs) and individuals with little to no videogame experience (NVGPs) performed on a task switching paradigm that provides a relatively well-established diagnostic measure of cognitive flexibility. As predicted, VGPs showed smaller switching costs (i.e., greater cognitive flexibility) than NVGPs. Our findings support the idea that playing FPS games promotes cognitive flexibility.